PENGEMBANGAN BUKU CERITA BERGAMBAR UNTUK MENINGKATKAN SIKAP MANDIRI SISWA PADA MATA PELAJARAN PENDIDIKAN PANCASILA KELAS I SEKOLAH DASAR - Sri Hartinah Pasha Carolin; Titin Sunaryati (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This research is motivated by the low level of independence and the minimal availability of picture story books. The purpose of this study is to improve student independence in Pancasila education subjects with picture story books. This study uses Development with the ADDIE model. The feasibility test was carried out by three validation experts, namely material experts with a percentage value of 96%, language experts with a percentage of 88%, and media experts with a percentage of 94%. The validation results of the three experts showed that the media developed was worthy of being tested. This is also supported by the effectiveness of the media as seen from the increase in student independence before using the media and after using the media with the N-Gain calculation which produced 0.74 with a high category. So it can be concluded that picture story books can improve student independence.